2005
DOI: 10.1258/rsmvasc.13.4.222
|View full text |Cite
|
Sign up to set email alerts
|

Rare Forms of Peripheral Arterial Embolism: Review of 11 Cases

Abstract: The purpose of this study was to present 11 patients operated on owing to rare forms of peripheral arterial embolism at the Institute for Cardiovascular Diseases of the Serbian Clinical Center over a period of 20 years. Three patients were operated on owing to a foreign body embolism, two owing to a septic embolism, three owing to emboli that originated from malignant tissues, two owing to an embolization from cardiac myxoma, and one owing to an embolism from a myxomatous atrial septal defect. The preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Arterial aneurysms followed by ulcerated atherosclerotic plaques of the major arteries are the second most common source of the emboli. 14 Unlike our patient, most patients with aortic embolic disease secondarily to atherosclerosis, are typically elderly with multiple comorbid conditions. 15 In our otherwise healthy patient, lipid profile was within normal levels, and by imaging tests, neither localised nor generalised atherosclerotic disease was detected.…”
Section: Discussionmentioning
confidence: 72%
“…Arterial aneurysms followed by ulcerated atherosclerotic plaques of the major arteries are the second most common source of the emboli. 14 Unlike our patient, most patients with aortic embolic disease secondarily to atherosclerosis, are typically elderly with multiple comorbid conditions. 15 In our otherwise healthy patient, lipid profile was within normal levels, and by imaging tests, neither localised nor generalised atherosclerotic disease was detected.…”
Section: Discussionmentioning
confidence: 72%
“…Acute arterial occlusion secondary to malignant tumor embolism is rare. Miroslav et al reviewed 877 cases of arterial emboli, of which only three cases (0.3%) of ATE were identified [ 1 ]. Xiromeritis et al reported that the majority (89.4%) of ATE were associated with primary lung cancer (44.2%), secondary lung cancer (31.7%), and primary tumors of the aorta (13.4%) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis and secondary embolism can also be associated with cancer, pregnancy, and hypercoagulation states, and in 10% of patients the source of peripheral embolism cannot be identified [3]. …”
Section: Discussionmentioning
confidence: 99%
“…In our first case, in fact, we performed clinical examination, laboratory findings, electrocardiography and finally-angio-CT scan to exclude rare forms such as foreign- body embolism, septic embolism, embolism from malignant tissues, embolization from cardiac myxoma or from a myxomatous atrial septal defect [3]. …”
Section: Discussionmentioning
confidence: 99%